2003
DOI: 10.3201/eid0901.020112
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Hand, Foot and Mouth Disease Caused by Human Enterovirus 71, Singapore

Abstract: Singapore experienced a large epidemic of hand, foot and mouth disease (HFMD) in 2000. After reviewing HFMD notifications from doctors and child-care centers, we found that the incidence of HFMD rose in September and declined at the end of October. During this period, 3,790 cases were reported. We performed enteroviral cultures on 311 and 157 specimens from 175 HFMD patients and 107 non-HFMD patients, respectively; human enterovirus 71 (HEV71) was the most frequently isolated virus from both groups. Most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 17 publications
7
156
0
Order By: Relevance
“…This finding is probably because our expanded surveillance detected more patients with neurologic disease. Since 1997, multiple cases of EV71 infection have been associated with severe aseptic meningitis and pulmonary edema in the Asia–Pacific region, including Taiwan, Malaysia, Singapore, and Japan ( 26 , 32 37 ). In addition, E30 was the second most common genotype detected during this period in this study and in previous studies from other countries; Asia and European countries reported that E30 was the predominant genotype ( 1 , 4 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is probably because our expanded surveillance detected more patients with neurologic disease. Since 1997, multiple cases of EV71 infection have been associated with severe aseptic meningitis and pulmonary edema in the Asia–Pacific region, including Taiwan, Malaysia, Singapore, and Japan ( 26 , 32 37 ). In addition, E30 was the second most common genotype detected during this period in this study and in previous studies from other countries; Asia and European countries reported that E30 was the predominant genotype ( 1 , 4 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…HFMD diagnosis was based on fever, oral ulcers, and maculopapular or vesicular rash on the hands and feet, with or without buttock involvement [7]. The diagnosis of brainstem encephalitis was based on neurological symptoms associated with the brainstem such as myoclonus with tremor and/or ataxia, myoclonus with cranial nerve involvement, and rapid cardiopulmonary failure [1].…”
Section: Clinical Datamentioning
confidence: 99%
“…Outbreaks have been reported in Malaysia (1997) [8], Taiwan (1998) [1], Australia (1999) [9], Singapore (2000) [10], Vietnam (2005) [11], and China (2008) [12], among other areas in the region. As global efforts to eradicate poliovirus-associated poliomyelitis proceed, EV71 has emerged as an important neurological threat to replace it.…”
Section: Introductionmentioning
confidence: 96%